PENDAMPINGAN PUBLIKASI ILMIAH GURU SMA N 1 MOJOTENGAH, WONOSOBO, JAWA TENGAH - Ahmad Khoiri; Marwiati Marwiati; Achmad Affandi; Kurniawati Mutmainah; Nurma Khusna Khanifa (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2022)
Scientific publications for teachers are very important to contribute in solving student problems in school. PKMTN goal is to increase the motivation and culture of writing teacher scientific publications at SMA N 1 Mojotengah Wonosobo. The method of service carried out with the principle of "service mastery" is identification of teachers targeted for scientific publications, preparation of articles according to the scope and guideline of the journal, assistance in submitting and reviewing journals and assisting publications. The study subject consisted of 26 high school teachers N 1 Mojotengah from a variety of different subjects. The results of the service activities showed that 65.7% of the program was carried out and the level of understanding of teachers in scientific publications in the medium category of scientific publications. The output produced is only 40% of teachers who are able to publish articles to the national scientific journal ISSN and the national journal accredited SINTA. The obstacles faced in the form of lack of teacher references in writing habits, writing articles only for the benefit of increasing the rank of saj